Unravelling the Biology of EhActo as the First Cofilin From Entamoeba histolytica - Kumar, Nitesh; Rath, Pragyan Parimita; Aggarwal, Priyanka; Maiti, Sankar; Bhavesh, Neel Sarovar; Gourinath, Samudrala (Frontiers in Cell and Developmental Biology, 2022)
Actin-depolymerising factors (ADF) are a known family of proteins that regulate actin dynamics. Actin regulation is critical for primitive eukaryotes since it drives their key cellular processes. Entamoeba histolytica, a protist human pathogen harbours eleven proteins within this family, however, with no actin depolymerising protein reported to date. We present here the NMR model of EhActo, the first Cofilin from E. histolytica that severs actin filaments and also participates in cellular events like phagocytosis and pseudopod formation. The model typically represents the ADF-homology domain compared to other cofilins. Uniquely, EhActo lacks the critical Serine3 residue present in all known actophorins mediating its phospho-regulation. The second mode of regulation that cofilin’s are subjected to is via their interaction with 14-3-3 proteins through the phosphorylated Serine residue and a consensus binding motif. We found a unique interaction between EhActo and 14-3-3 without the presence of the consensus motif or the phosphorylated Serine. These interesting results present unexplored newer mechanisms functional in this pathogen to regulate actophorin. Through our structural and biochemical studies we have deciphered the mechanism of action of EhActo, implicating its role in amoebic biology.